Technical Efficiency and Its Influence on The Growth of The Manufac- turing Sector in East Java: A Case Study on The Gerbangkertasusila Plus Development Area - Suhindarto; Yulya Aryani; Wina Andari (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2020)
The manufacturing industry has emerged as key sectors to the national and regional economic growth in East Java. This study estimates the efficiency of the manufacturing industry in East Java and analyzes the factors that influence the industrial sector using the efficiency value as one of the explanatory factors. The object of this research is the manufacturing industry in regency and/or cities in East Java for the period 2012-2015. The results showed that Tuban Regency, Pasuruan Regency, Sidoarjo Regency, Mojokerto City, and Surabaya City were a region that had relatively efficient industrial efficiency values during the 2012-2015 period. However, the average change in total production for all manufacturing industries in the Gerbangkertasusila Plus Development Area during 2012-2015 showed a decline. Moreover, the level of labor utilization and capital expenditure are a determining factor in the level of productivity of the manufacturing industry in East Java.